Performance Test of Animal Feed Chopping Machine with Electric Motor Drive - Erwin, Erwin (Devotion : Journal of Research and Community Service, 2025)
Animal feed is a crucial factor influencing animal productivity and health. Ensuring the availability of high-quality feed, both in terms of nutritional content and physical appearance, is essential. One way to improve the physical quality of feed is through the shredding process using a shredding machine. This study aimed to test the performance of the shredding machine in processing two types of animal feed: sedge grass and banana stems. The research method used an experimental approach with three repetitions, including measuring effective capacity, cutting uniformity, and percentage of material loss. The test results showed that the machine's effective capacity was more optimal for sedge grass, at 38 kg/hour, compared to 34 kg/hour for banana stems. The cutting uniformity values were relatively similar, at 80.2% for sedge grass and 80.0% for banana stems. The percentage of material loss for sedge grass was 2.6%, significantly lower than for banana stems, which reached 9.2%. This indicates that the machine is more efficient when used on soft, fine-fibered materials. Compared to previous studies, the machine's capacity in this study was still significantly lower due to limited motor power (500 watts) and a simple blade design. However, the machine is capable of producing uniform cuts and quite good efficiency, especially on the grass material.